Potential of Fish Protein Hydrolysates as Bioactive Ingredients for Antidiabetic Functional Snacks: A Narrative Review - Rahma Agniya Nugraha; Ahmad Syauqy; Diana Nur Afifah (Media Publikasi Cendekia Indonesia, 2026)
The rising prevalence of diabetes mellitus highlights the need for food-based strategies that reduce postprandial glycaemic excursions. Snacks are a critical dietary target due to their frequent consumption, yet most commercial options are rich in rapidly digestible carbohydrates. Fish protein hydrolysates (FPHs) offer peptide-mediated bioactivity beyond simple macronutrient substitution, but their application in antidiabetic snack development remains limited. This review evaluates the potential of FPHs as functional ingredients in antidiabetic snack formulations. A narrative synthesis of literature from major scientific databases was performed, focusing on antidiabetic mechanisms of FPH-derived peptides and their incorporation into finished snack products. Evidence suggests that FPHs may support glycaemic regulation through inhibition of α-amylase, α-glucosidase, and DPP-IV, modulation of incretin pathways including GLP-1, and antioxidant activity, mainly demonstrated in in vitro and in vivo models. Product studies indicate that FPH incorporation at optimal levels of approximately 2–15% improves protein density and digestibility in snack matrices such as cookies, biscuits, bars, noodles, and bread. However, sensory acceptance is formulation-dependent, and bitterness or fishy off-flavours may require mitigation strategies such as enzymatic debittering or fermentation. Despite promising functional properties, human evidence confirming glycaemic benefits of FPH-enriched snacks remains limited. Standardized characterization and well-controlled clinical trials using finished products are essential to translate mechanistic potential into validated dietary applications.